2024
DOI: 10.1371/journal.pone.0300894
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder and associated factors among internally displaced persons in Africa: A systematic review and meta-analysis

Amensisa Hailu Tesfaye,
Ashenafi Kibret Sendekie,
Gebisa Guyasa Kabito
et al.

Abstract: Background Internally displaced people (IDPs), uprooted by conflict, violence, or disaster, struggle with the trauma of violence, loss, and displacement, making them significantly more vulnerable to post-traumatic stress disorder (PTSD). Therefore, we conducted a systematic review and meta-analysis to assess the prevalence and associated factors of PTSD among IDPs in Africa. Methods A comprehensive search of electronic databases was conducted to identify relevant studies published between 2008 and 2023. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(158 reference statements)
1
1
0
Order By: Relevance
“…According to the subgroup analysis report a higher prevalence of PTSD was found among participants in IDP settings than in community-based study settings. This finding of this result is supported by previous studies conducted in Africa ( 46 , 47 ). The possible justification for this discrepancy might be due to trauma exposure which is an individual in IDP settings may have experienced higher levels of trauma due to forced displacement, conflict, or natural disasters compared to those in stable community settings.…”
Section: Discussionsupporting
confidence: 91%
“…According to the subgroup analysis report a higher prevalence of PTSD was found among participants in IDP settings than in community-based study settings. This finding of this result is supported by previous studies conducted in Africa ( 46 , 47 ). The possible justification for this discrepancy might be due to trauma exposure which is an individual in IDP settings may have experienced higher levels of trauma due to forced displacement, conflict, or natural disasters compared to those in stable community settings.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, our study found that only 33.5% of the participants had comorbid depression. Various studies have shown that having comorbid depression can elevate the risk of developing post-traumatic stress disorder ( 28 , 29 , 73 75 ). Another reason for this discrepancy could be the differences in the assessment tools, study designs, and the type and degree of exposure experienced by the participants in these studies.…”
Section: Discussionmentioning
confidence: 99%